Floral Color Variation in Drosera cistiflora Is Associated With Switches in Beetle Pollinator Assemblages - Johnson, Steven D.; von Witt, Caitlin G.; Anderson, Bruce (Frontiers in Plant Science, 2020)
Floral colour shifts are thought to be one of the most common evolutionary transitions in plants, and pollinators are often proposed as important selective agents driving these transitions. However, shifts in flower colour can also be related to neutral genetic processes or pleiotropy linked with selection via other biotic agents or abiotic factors. Here we ask whether abiotic factors or pollinators provide the best explanation for divergence in flower colour among populations of the sundew Drosera cistiflora s.l. (Droseraceae). This species complex in the Greater Cape Floristic Region contains at least five distinctive floral colour forms. Abiotic factors do not appear to play a significant role in colour determination, as the forms are not specific to a single soil or vegetation types, sometimes co-occur in the same habitat, and maintain their colour traits in common-garden and soil switching experiments. Instead, we found strong associations between flower colour and the composition of pollinator assemblages which are dominated by hopliine scarab beetles. Pollinator assemblages show geographical structuring, both within and among colour forms. This makes it difficult to dissect the roles of geography versus floral traits in explaining pollinator assemblages, but strong pollinator partitioning among colour forms at sites where they are sympatric indicates that pollinators may select strongly on colour. These results suggest that beetle pollinators are a significant factor in the evolution of D. cistiflora s.l. flower colour.